Field investigation to assess performance of polymeric lining used in renewal of sewers in buildings - Dataset - Kharazmi, Parastou (Royal Institute of Technology, 2019)
This dataset includes original data provided to support parts of the research findings stated in article: "Experimental assessment of the state of the lining materials used in the rehabilitation of sewers in residential buildings”.

The dataset was originally published in DiVA and moved to SND in 2024.

Detta datasetet innehåller originaldata som tillhandahålls för att stödja delar av forskningsresultaten som anges i artikeln: "Experimental assessment of the state of the lining materials used in the rehabilitation of sewers in residential buildings”.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Field investigation to assess performance of polymeric lining used in renewal of sewers in buildings - Dataset
Keywords: house construction; husbyggnad; sewers; avloppsledningar; Building Technologies; Husbyggnad; Other Civil Engineering; Annan samhällsbyggnadsteknik; Reliability and Maintenance; Tillförlitlighets- och kvalitetsteknik; Composite Science and Engineering; Kompositmaterial och kompositteknik; Other Materials Engineering; Annan materialteknik